Telaah Produk Monograf dari Hasil Simulasi dan Visualisasi Gelombang 2D dan 3D pada Membran Lingkaran dengan Software Scilab - Dwi Nova Siti Handayani; Yudhiakto Pramudya; Suparwoto Suparwoto (Jurnal Penelitian Pembelajaran Fisika, 2020)
This study aims to produce the monograph of the simulation and visualization of 2D and 3D wave on the circular membrane with Scilab Software for Physics and Physics Education students. The research method used was experimental research which produced a reference book in the form of a research monograph. This monograph was validated by physics education lecturers, educators,and physics education students. Data collection techniques were carried out by collecting questionnaires in the form of expert validation sheets (material and media), educator / lecturer response sheets, and student response sheets. The data obtained from the validation test are in the form of a percentage of the validity of the monograph from the validation of two material experts and two media experts, the average score are 91% and 90%. The monograph test by three educators and the response test by 15 students the average score are 89% and 88%. The results of the validation test of the material expert, media expert, educators response, and the response of the students are the very good so that it can be concluded that the monograph product can be used as a learning media in the form of reference books in vibration and wave learning.